A modified polyphenylene sulfide composite material and a preparation method thereof
Patent Information
- Application Number
- CN202611420366.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-27
AI Technical Summary
(1)在总固体体积分数相同的条件下,以不熔性有机微球部分替代球形无机微球,体系熔体粘度不升反降,突破了本领域提高填充量必然升高粘度的技术偏见,使高填充体系仍可稳定落在340℃、900s-¹下不高于600Pa·s的可精密成型窗口内。在不提高线膨胀系数的前提下,显著改善260℃回流焊后的孔位稳定性。
Smart Images

Figure SMS_8 
Figure SMS_9 
Figure SMS_10
Abstract
Description
Technical Field
[0001] This invention relates to the field of PPS material technology, specifically to a modified polyphenylene sulfide composite material and its preparation method. Background Technology
[0002] Mechanically mated (MT) ferrules are the core precision components of multi-fiber connectors, featuring multiple fiber optic holes and a pair of guide pin holes on their end faces. To achieve low insertion loss, the cores of the multiple fibers must be precisely aligned. This requires the ferrule material to possess a low coefficient of linear expansion, high dimensional stability, resistance to reflow soldering temperatures up to 260°C, good precision moldability, and low moisture absorption and resistance to environmental aging. Polyphenylene sulfide (PPS) is the preferred matrix resin for MT ferrules due to its excellent heat resistance, extremely low water absorption, inherent flame retardancy, and low melt viscosity. However, the coefficient of linear expansion of pure PPS differs from that of silica fiber by nearly two orders of magnitude, and as a semi-crystalline polymer, it tends to continue crystallizing after molding, making it unsuitable for directly meeting the dimensional stability requirements of the ferrule.
[0003] Therefore, the use of highly filled spherical inorganic microspheres is commonly adopted in this field. Chinese invention patent CN114350151B discloses a composite material of 55%~85% modified silica and 14%~44% PPS, with the first paragraph of its specification explicitly stating that "the raw material for the MT insert is mainly a blend of PPS and SiO2 microspheres." However, there is a clear upper limit to the amount of inorganic filler. European patent EP1031859 points out that if the silica content exceeds 65wt%, the fluidity of the PPS resin decreases, potentially leading to molding failure. US patent US6347890 provides a viscosity criterion generally accepted in the field: at 340°C and 900s... - Under these conditions, a PPS composition containing 250–300 parts by weight of silica and 10–70 parts by weight of whiskers has a melt viscosity of 300–600 Pa·s. Since the reduction in the coefficient of linear expansion depends on the increase in filler content, this flow ceiling directly limits the potential for further improvement in the dimensional stability of the composite material.
[0004] In summary, existing technologies face mutually restrictive challenges in preparing high-dimensionally stable PPS ferrule materials: reducing the coefficient of linear expansion requires increasing the filler content, which is constrained by melt flowability; while multi-particle-size gradation can increase filler density, the potential for improvement in the high-filler range is very limited; in the blending route that introduces heat-resistant resin, amorphous resin is in a molten state at the processing temperature and requires high shear dispersion, and its dispersed phase morphology is unstable in subsequent thermal history and increases the viscosity of the system; while replacing spherical fillers with whiskers can alleviate the flowability problem, it introduces anisotropy, which contradicts the dimensional accuracy requirements of the ferrule; in addition, the post-crystallization tendency of PPS requires stabilization of the crystallization state through post-treatment such as annealing, but the annealing process is independent of the molding process and cannot maintain the pore position constraint during crystallization.
[0005] It is worth noting that the above-mentioned existing mixing routes, whether it is graded blending of multi-peak spherical fillers or compatibilizing blending of amorphous resin, all involve first pre-mixing the resin phase by melt, and then adding the filler or dispersed phase; there is no teaching in the art on first constructing a high-density packing skeleton on the filler side and then impregnating it with molten resin.
[0006] Therefore, there is still an urgent need in the field for a polyphenylene sulfide composite material that can simultaneously achieve a low coefficient of linear expansion, high dimensional stability, good melt flowability, and isotropy at higher filler contents. Summary of the Invention
[0007] The purpose of this invention is to overcome at least one of the defects of the prior art and provide a modified polyphenylene sulfide composite material and its preparation method, so as to obtain a polyphenylene sulfide composite material with low coefficient of linear expansion, high dimensional stability, good melt flowability and isotropy.
[0008] Specifically, this invention provides a modified polyphenylene sulfide composite material, comprising polyphenylene sulfide, spherical inorganic microspheres, and infusible organic microspheres; based on 100 parts by mass of polyphenylene sulfide, the spherical inorganic microspheres comprise 280-450 parts, and the infusible organic microspheres comprise 2-40 parts; the spherical inorganic microspheres have three particle size peaks: fine peak, medium peak, and coarse peak, wherein the D50 values of the fine peak, medium peak, and coarse peak are 60-100 nm, 0.5-2.5 μm, and 5-15 μm, respectively; the glass transition temperature of the infusible organic microspheres is not lower than 300℃, and the D50 of the infusible organic microspheres is 0.15-0.5 times that of the medium peak and 1.5-8 times that of the fine peak. In an embodiment of this invention, the total integral of the spherical inorganic microspheres and the infusible organic microspheres in the modified polyphenylene sulfide composite material is 68%-72%.
[0009] Furthermore, the infusible organic microspheres are at least one of cross-linked polyimide or its copolymer microspheres, bio-based epoxy resin microspheres, and polysulfonated aromatic amide.
[0010] Furthermore, the infusible organic microspheres are cross-linked polyimide microspheres, wherein the sphericity of the cross-linked polyimide microspheres is ≥0.85, and the particle size distribution span (D90) is [missing information]. D10 / D50 ≤ 1.5; the gel content of the cross-linked polyimide microspheres is ≥ 85%.
[0011] Furthermore, the infusible organic microspheres are cross-linked resveratrol-based bio-based epoxy resins, wherein the phenolic hydroxyl content of the bio-based epoxy resin is not less than 0.5 mmol / g.
[0012] Furthermore, the spherical inorganic microspheres are selected from one or more of alumina, silicon oxide, and magnesium aluminate, the sphericity of the spherical inorganic microspheres is ≥0.90, the sphericity of the coarse peak is ≥0.93, and the true density of the spherical inorganic microspheres is 2.0~4.5 g / cm³.
[0013] Furthermore, the surface of the spherical inorganic microspheres has a silane coupling agent layer, and the amount of the silane coupling agent layer is 0.5 to 12 parts per 100 parts by weight of polyphenylene sulfide.
[0014] Furthermore, the volume fractions of the fine peaks, medium peaks, and coarse peaks in the total volume of the spherical inorganic microspheres are 5%~15%, 20%~35%, and 50%~70%, respectively; the sum of the volume fractions of the fine peaks, medium peaks, and coarse peaks is 100%.
[0015] Furthermore, the ratio of the D50 of the intermediate peak to the D50 of the coarse peak is 1:2 to 1:30, and the ratio of the D50 of the fine peak to the D50 of the intermediate peak is 1:5 to 1:50.
[0016] The present invention also provides a method for preparing the above-mentioned modified polyphenylene sulfide composite material, comprising a low-temperature pre-stacking section and a high-temperature impregnation section performed sequentially: S1. Spherical inorganic microspheres and infusible organic microspheres are mixed in a twin-screw extruder at 120~200℃, 50~200r / min and residence time of 60~300s to obtain a pre-packed particle aggregate. The tapped density of the pre-packed particle aggregate is not less than 1.05 times the tapped density of the spherical inorganic microspheres alone. S2. Polyphenylene sulfide is added and melted through the main feed port of the twin-screw extruder. The pre-stacked particle aggregate is added to the molten polyphenylene sulfide through the side feed port located after the melting section. The mixture is blended at 290~340℃, with a screw speed of 200~600 r / min, a residence time of 30~180 s, and a melt average shear rate of 500~5000 s. - ¹, when the vacuum degree ≤ Exhaust gas at 0.06 MPa and extrude pellets.
[0017] Furthermore, it also includes S3: after drying the pellets obtained by pelletizing at 120~140℃ for ≥4h, they are injection molded, and then annealed at 190~215℃ for 30~180min, with a cooling rate of 10~40℃ / h.
[0018] In some preferred embodiments of the present invention, the surface of the infusible organic microspheres does not contain a coupling agent layer or compatibilizer, and the interface between the microspheres and the polyphenylene sulfide matrix is a physical contact interface. That is, only the spherical inorganic microspheres undergo silane surface treatment in the system, while the infusible organic microspheres are not subjected to any coupling, grafting, or compatibilization treatment, allowing them to directly contact the polyphenylene sulfide matrix with their native surfaces. The inventors have found that if coupling agents or compatibilizers are also applied to the infusible organic microspheres, the interface between the organic microspheres and the matrix is anchored, the interface slippage ability is lost, the melt viscosity of the system increases, and the center distance offset of the guide pin holes after reflow soldering at 260°C is significantly worsened.
[0019] In some preferred embodiments of the present invention, the infusible organic microspheres exist as discrete, independent particles in the gaps formed by the stacking of the spherical inorganic microspheres, without encapsulating the spherical inorganic microspheres or forming a core-shell structure with them.
[0020] In some preferred embodiments of the present invention, the D50 of the infusible organic microspheres is between that of the fine peak and the medium peak. Studies have found that organic microspheres with particle sizes at this level can act as a submicron-scale dispersion medium in the S1 low-temperature solid-state mixing section: since the fine peaks are nanoscale particles of 60-100 nm, they significantly agglomerate in the dry state due to van der Waals effects. The dense agglomerates cannot effectively enter the gaps formed by the accumulation of medium and coarse peaks, thus limiting the packing density of spherical inorganic microspheres when vibrated individually. Introducing infusible organic microspheres with a D50 between the fine and medium peaks allows these microspheres to shear and break up the fine peak agglomerates and carry them away during low-speed solid-state mixing, promoting the filling of the gaps between the medium and coarse peaks by the fine peaks. This results in a tap density of the pre-packed particle aggregate that is more than 5% higher than the tap density of spherical inorganic microspheres when vibrated individually. When the D50 of organic microspheres is less than 1.5 times that of fine peaks, they tend to aggregate and cannot function as a dispersion medium; when the D50 of organic microspheres is greater than 0.5 times that of medium peaks, they cannot enter the target interstitial layer and thus cannot increase the packing density.
[0021] In some preferred embodiments of the present invention, the weight-average particle size and sphericity of the non-meltable organic microspheres are determined by the test methods described below, and the gel content is ≥85%, thereby ensuring that they do not melt or collapse at the processing temperature of 290~340℃ in the S2 section, and maintain a rigid particle morphology throughout the annealing process in the S3 section and the reflow soldering process at 260℃, thus forming a thermally stable rigid skeleton.
[0022] In some preferred embodiments of the present invention, the relative bulk density (ratio of tapped density to true density of the aggregate) of the pre-stacked particle aggregate is 0.72 to 0.88, so as to obtain the highest possible rigid particle volume fraction while ensuring that the molten polyphenylene sulfide in section S2 can be fully impregnated.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Under the same total solid volume fraction, when infusible organic microspheres are partially replaced with spherical inorganic microspheres, the melt viscosity of the system decreases instead of increasing. This breaks through the technical prejudice in the field that increasing the filling amount will inevitably increase the viscosity, and allows the high-filling system to remain stable at 340℃ and 900s. - ¹Within a precision-formable window not exceeding 600 Pa·s. Significantly improves hole stability after reflow soldering at 260℃ without increasing the coefficient of linear expansion.
[0024] (2) The S1 low-temperature pre-stacking section enables the infusible organic microspheres to act as a dispersion medium, thereby breaking the agglomeration of nano-fine peaks and increasing the packing density. The tap density of the pre-stacking particle aggregate is more than 1.05 times that of the tap density of the spherical inorganic microspheres alone, thus accommodating a higher volume fraction of rigid particles at the same viscosity.
[0025] (3) The inorganic microspheres are kept spherical and treated with silane, while the organic microspheres are not surface treated. The resulting composite material has good isotropy and does not introduce the molding anisotropy and dimensional accuracy deterioration problem caused by whisker fillers.
[0026] (4) When cross-linked resveratrol-based bio-based epoxy resin microspheres are selected as infusible organic microspheres in this invention, the phenolic hydroxyl groups retained in their molecular skeleton can capture free radicals of thermo-oxidative aging, which can further significantly improve the processing thermal stability and long-term thermo-oxidative aging resistance of the composite material: the oxidation induction period is increased to more than 3 times that of the pure inorganic system, the melt viscosity change rate at 340℃ for 30 min is reduced from +28% to +7%, and the flexural strength retention rate after 175℃ for 1000 h of heat aging is increased from 68% to 93%, thereby obtaining significantly better durability while maintaining pore stability.
[0027] (5) The amount of spherical inorganic microspheres used in this invention is 280-450 parts per 100 parts by weight of polyphenylene sulfide; the mass fraction of spherical inorganic microspheres is 73.7%-81.8% when the total mass of polyphenylene sulfide and spherical inorganic microspheres is 100%; and the mass fraction of spherical inorganic microspheres is 66.7%-81.5% when the total mass of the composite material (i.e., including the infusible organic microspheres). Due to the introduction of the infusible organic microspheres, the melt viscosity of the system can still be maintained at 340℃ for 900s. -¹Within a precision molding window of no more than 600 Pa·s, a low coefficient of linear expansion, high pore stability, and good molding flowability can be obtained simultaneously at higher filling amounts. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described below with reference to specific embodiments, but the scope of protection of this invention is not limited thereto. Experimental methods not specifically described in the embodiments are generally performed under conventional conditions or according to the manufacturer's recommendations. Unless otherwise specified, all reagents and materials used are commercially available.
[0029] I. Raw Materials Polyphenylene sulfide (PPS): Melt index 120g / 10min (316℃, 5kg), melting point 280℃, true density 1.35 g / cm³, commercially available.
[0030] Spherical inorganic microspheres: Spherical silica (true density 2.20 g / cm³), spherical alumina (true density 3.95 g / cm³), and spherical magnesium aluminate (true density 3.60 g / cm³) are all spherical powders prepared by melt method, commercially available, and used after being graded according to the particle size required in the examples; the sphericity of the above spherical silica, spherical alumina, and spherical magnesium aluminate were measured to be 0.94, 0.92, and 0.91, respectively, of which the spherical silica constituting the coarse peak had a sphericity of 0.95.
[0031] Infusible organic microspheres A: Cross-linked polyimide microspheres, true density 1.35 g / cm³, glass transition temperature 345℃, gel content 92%, sphericity 0.90, particle size distribution span 1.2, commercially available.
[0032] Infusible organic microspheres B: Cross-linked resveratrol-based bio-based epoxy resin microspheres, true density 1.30 g / cm³, glass transition temperature 305℃, gel content 88%, sphericity 0.88, particle size distribution span 1.4, phenolic hydroxyl content 0.82 mmol / g (determined by hydrochloric acid-acetone titration), commercially available.
[0033] Meltable organic microspheres (for comparative example): Polyetherimide (PEI) microspheres, true density 1.27 g / cm³, glass transition temperature 217℃, commercially available.
[0034] Infusible organic microspheres C (for comparative example): cross-linked bisphenol A type epoxy resin microspheres, true density 1.22 g / cm³, glass transition temperature 300℃, gel content 90%, sphericity 0.89, phenolic hydroxyl content 0.03 mmol / g, commercially available.
[0035] Silane coupling agent: Phenylacetyltrimethoxysilane, commercially available.
[0036] II. Testing Methods (1) Particle size D50, D90, D10 and three-peak distribution: The particle size was determined by wet method using a laser particle size analyzer (Malvern Mastersizer 3000). The dispersion medium was anhydrous ethanol. The dispersion was ultrasonic for 3 min. The refractive index was set according to each material. The volume fraction of the three peaks was given by peak fitting of the particle size distribution software.
[0037] (2) Sphericity: The sphericity was determined by a dynamic particle image analyzer. The number of particles in each sample was no less than 2,000. The sphericity was the average of the ratio of the particle's projected area to the area of its smallest circumscribed circle.
[0038] (3) Glass transition temperature Tg and melting endothermic peak: Differential scanning calorimetry (DSC) was used in a nitrogen atmosphere at a heating rate of 10℃ / min. The second heating curve was taken, and the glass transition temperature was taken at the midpoint of the baseline offset. The presence of melting endothermic peak was observed in the range of 100~350℃. The glass transition was manifested as a baseline offset and did not constitute a melting endothermic peak. When observing the melting endothermic peak, infusible organic microspheres were prepared separately and measured without polyphenylene sulfide matrix.
[0039] (4) Gel content: Soxhlet extraction was performed for 24 hours using N-methylpyrrolidone as solvent. The residue was dried at 150℃ to constant weight. Gel content = (mass of residue after extraction ÷ mass of sample before extraction) × 100%.
[0040] (5) Tap density: Measured according to the method specified in GB / T5162, with 3000 taps.
[0041] (6) Melt viscosity: Using a capillary rheometer, at 340℃ and a shear rate of 900s, the viscosity was measured. - ¹Measured below.
[0042] (7) Coefficient of linear expansion (CTE): determined according to ISO 11359-2 (thermomechanical analysis), temperature range 30~150℃, heating rate 5℃ / min, and flow direction.
[0043] (8) 260℃ reflow soldering hole position offset: The material is injection molded into a 12-core MT insert, and reflowed 3 times according to the lead-free reflow soldering curve (peak temperature 260℃) specified by IPC / JEDECJ-STD-020. The center distance between the two guide pin holes before and after reflow is measured by a two-dimensional image measuring instrument. The absolute value of the change is recorded as the hole position offset, in μm.
[0044] (9) Hole position offset increment after heat aging: After the refluxed core is placed at 150℃ for 1000h, the center distance between the two guide pin holes is measured again. The change in the value relative to the measured value after reflux is recorded as the hole position offset increment after heat aging, in μm.
[0045] (10) Bending strength: determined according to GB / T9341.
[0046] (11) Molding properties: Injection molding with a 12-core MT core mold, observe with the naked eye and under a microscope for short shots and missing materials, and those that are completely filled are recorded as "perfect".
[0047] (12) Oxidation induction period (OIT): determined according to GB / T 19466.6, test temperature 210℃, oxygen atmosphere, and take the exothermic peak at the start of oxidation time.
[0048] (13) Melt viscosity change rate: First, hold the temperature at 340℃ for 30 min, then follow the method described in (6) above at 340℃ for 900 s. - ¹The melt viscosity η1 was measured below. Let the viscosity of the untreated sample be η0, and the viscosity change rate be (η1-η0) / η0×100%.
[0049] (14) Bending strength retention rate after heat aging: The sample was placed at 175℃ for 1000 h, and then the bending strength σ1 was measured according to (10). With the strength of the unaged sample as σ0, the strength retention rate = σ1 / σ0 × 100%.
[0050] (15) Phenolic hydroxyl content: determined by hydrochloric acid-acetone titration method.
[0051] The formulation composition of Examples 1-5 and Comparative Examples 1-9 is shown in Table 1; the tap density and relative bulk density test results are shown in Table 2; the conventional performance test results are shown in Table 3; and the thermo-oxidative aging resistance test results are shown in Table 4.
[0052] Example 1 Based on 100 parts by weight of polyphenylene sulfide, take 380 parts by weight of spherical silica, which consists of fine peaks (D50=80nm, accounting for 10% of the total inorganic volume), medium peaks (D50=1.2μm, accounting for 30%), and coarse peaks (D50=9μm, accounting for 60%); take 15 parts by weight of infusible organic microspheres A (cross-linked polyimide microspheres), which has a D50=0.45μm (0.375 times the D50 of the medium peak and 5.6 times the D50 of the fine peak).
[0053] S1. The above spherical silica and infusible organic microspheres A are added to a twin-screw extruder and mixed at 160°C, 120 r / min and a residence time of 180 s to obtain a pre-stacked particle aggregate. S2. Add the pre-stacked particle aggregate to molten polyphenylene sulfide at 310℃, and blend at 310℃ with a screw speed of 400 r / min, a residence time of 90 s, and a melt average shear rate of 2200 s. - ¹, in vacuum degree Degassing and pelletizing at 0.08 MPa; S3. After drying the pellets obtained by pelletizing at 130℃ for 6 hours, they are injection molded and then annealed at 200℃ for 90 minutes with a cooling rate of 25℃ / h.
[0054] Example 2 Based on 100 parts by weight of polyphenylene sulfide, the spherical inorganic microspheres are composed of 243 parts by weight of spherical silica and 187 parts by weight of spherical alumina, totaling 430 parts by weight. Among them, the fine peak (D50 = 70 nm) is composed of 34.7 parts by weight of spherical silica, the medium peak (D50 = 1.5 μm) is composed of 187.0 parts by weight of spherical alumina, and the coarse peak (D50 = 12 μm) is composed of 208.3 parts by weight of spherical silica. The volume fractions of these three components in the total volume of the spherical inorganic microspheres are 10%, 30%, and 60%, respectively (the true density of spherical silica is 2.20 g / cm³, and the true density of spherical alumina is 3.95 g / cm³, so the corresponding volumes are 15.8 cm³, 47.3 cm³, and 94.7 cm³, respectively). Taking 6 parts by weight of infusible organic microspheres A, whose D50 = 0.42 μm (0.28 times the D50 of the mid-peak and 6.0 times the D50 of the fine-peak).
[0055] S1 was mixed at 180℃, 90 r / min, and a residence time of 240 s; S2 was mixed at 320℃, a screw speed of 350 r / min, a residence time of 110 s, and an average melt shear rate of 1800 s. - ¹ Vacuum degree The mixture was blended, extruded, and pelletized at 0.08 MPa; S3 was dried at 130℃ for 6 h and then injection molded, annealed at 205℃ for 120 min, and cooled at a rate of 20℃ / h.
[0056] Example 3 Based on 100 parts by weight of polyphenylene sulfide, take 300 parts by weight of spherical silica, which consists of fine peaks (D50=95nm, accounting for 14%), medium peaks (D50=0.7μm, accounting for 33%), and coarse peaks (D50=7μm, accounting for 53%); take 30 parts by weight of infusible organic microspheres A, which have a D50=0.28μm (0.40 times the D50 of the medium peak and 2.95 times the D50 of the fine peak).
[0057] S1 was mixed at 140℃, 150 r / min, and a residence time of 150 s; S2 was mixed at 300℃, a screw speed of 450 r / min, a residence time of 80 s, and an average melt shear rate of 2600 s. - ¹ Vacuum degree The mixture was blended, extruded, and pelletized at 0.08 MPa; S3 was dried at 130℃ for 6 h and then injection molded, annealed at 195℃ for 60 min, and cooled at a rate of 30℃ / h.
[0058] Example 4 Based on 100 parts by weight of polyphenylene sulfide, take 350 parts by weight of spherical silica, which consists of fine peaks (D50=85nm, accounting for 12%), medium peaks (D50=1.0μm, accounting for 30%), and coarse peaks (D50=8μm, accounting for 58%); take 20 parts by weight of infusible organic microspheres B (crosslinked resveratrol-based bio-based epoxy resin microspheres), which has a D50=0.35μm (0.35 times the D50 of the medium peak and 4.1 times the D50 of the fine peak).
[0059] S1 was mixed at 150℃, 130 r / min, and a residence time of 200 s; S2 was mixed at 305℃, a screw speed of 420 r / min, a residence time of 85 s, and an average melt shear rate of 2400 s. - ¹ Vacuum degree The mixture was blended, extruded, and pelletized at 0.08 MPa; S3 was dried at 130℃ for 6 h and then injection molded, annealed at 198℃ for 75 min, and cooled at a rate of 28℃ / h.
[0060] Example 5 The formulation is the same as in Example 1, except that: the spherical silica is pre-treated with phenyltrimethoxysilane, and the amount of silane used is 3 parts per 100 parts by weight of polyphenylene sulfide (i.e., the spherical silica and silane are mixed in a high-speed mixer at 80°C for 15 minutes and then set aside); the infusible organic microspheres A are not subjected to any surface treatment. The preparation process parameters are the same as in Example 1.
[0061] Comparative Example 1 Based on 100 parts by weight of polyphenylene sulfide, 380 parts by weight of spherical silica were taken, with the same gradation as in Example 1 (80nm / 1.2μm / 9μm=10 / 30 / 60), without adding any organic microspheres. The process was the same as in Example 1.
[0062] Comparative Example 2 The 15 parts by mass of the infusible organic microspheres A in Example 1 were converted into spherical silica by volume conversion. The conversion process is as follows: Volume of organic microsphere A = 15 ÷ 1.35 = 11.11 cm³, Mass of spherical silica of equal volume = 11.11 × 2.20 = 24.4 parts by mass. Therefore, the total amount of spherical silica used = 380 + 24.4 = 404.4 parts by mass. The gradation ratio is the same as in Example 1, without adding any organic microspheres. This comparative example has the same total solid volume fraction as Example 1, only the particle type is different. The process is the same as in Example 1.
[0063] Comparative Example 3 The formulation is the same as in Example 1, but the infusible organic microspheres A are replaced with an equal mass of polyetherimide (PEI) microspheres (Tg=217℃, D50=0.45μm). The process is the same as in Example 1.
[0064] Comparative Example 4 The formulation is the same as in Example 1, but the D50 of the infusible organic microspheres A is 0.08 μm, which is only 1.0 times that of the fine peak D50, lower than the 1.5 times lower limit specified in this invention. The process is the same as in Example 1.
[0065] Comparative Example 5 The formulation is the same as in Example 1, but the D50 of the infusible organic microspheres A is 0.96 μm, which is 0.8 times the D50 of the mid-peak, higher than the upper limit of 0.5 times specified in this invention. The process is the same as in Example 1.
[0066] Comparative Example 6 Based on 100 parts by weight of polyphenylene sulfide, 380 parts by weight of spherical silica with a single particle size peak (D50=9μm) were taken, without the addition of any organic microspheres. The process was the same as in Example 1.
[0067] Comparative Example 7 The formulation is the same as in Example 5, except that in addition to the spherical silica being treated with silane, the infusible organic microspheres A are also treated with phenyltrimethoxysilane (1.5 parts silane based on 100 parts by weight of polyphenylene sulfide), meaning that a coupling agent layer also exists on the surface of the organic microspheres. The process is the same as in Example 1.
[0068] Comparative Example 8 The formulation is the same as in Example 1, but the S1 low-temperature pre-stacking section is omitted. Spherical silica, infusible organic microspheres A, and polyphenylene sulfide are melt-blended at 310°C in a single operation (screw speed 400 r / min, residence time 90 s, vacuum degree). (0.08MPa), extrusion pelletizing; S3 is the same as in Example 1.
[0069] Comparative Example 9 The formulation is the same as in Example 4, but the infusible organic microspheres B (based on resveratrol, phenolic hydroxyl content 0.82 mmol / g) are replaced with an equal mass of cross-linked bisphenol A type epoxy resin microspheres (infusible organic microspheres C, phenolic hydroxyl content 0.03 mmol / g, Tg = 300℃, D50 = 0.35 μm). The process is the same as in Example 4.
[0070] III. Formulation and Performance Test Results Table 1 Formulation composition of the examples and comparative examples (parts by weight, based on 100 parts by weight of PPS)
[0071] Table 2 Tap density and relative bulk density
[0072] Table 3 Comprehensive Performance Test Results
[0073] Table 4 Test results of resistance to thermo-oxidative aging
[0074] IV. Results Analysis 4.1 Isovolute Replacement Reversal Experiment According to well-known suspension viscosity theories (such as the Krieger-Dougherty relationship), under conditions of identical particle shape (both spherical) and total integral, the system viscosity should be determined by the volume fraction, and the two should be essentially equivalent. Furthermore, since the intrinsic modulus of polyimide microspheres is lower than that of silica, a lower system viscosity is generally not expected. However, the measured results were the opposite: the melt viscosity of Example 1 was 558 Pa·s, while that of Comparative Example 2 was 645 Pa·s. When the infusible organic microspheres occupied this volume, the system viscosity actually decreased by approximately 13.5%.
[0075] More notably, the 645 Pa·s of Comparative Example 2 exceeded the 300-600 Pa·s precision molding window, resulting in short shots on the 12-core MT insert mold; while the 558 Pa·s of Example 1 remained stably within this window, with excellent molding. This result demonstrates that, under the premise of the same total solids volume fraction, replacing some spherical inorganic microspheres with infusible organic microspheres not only does not worsen the flowability but also transforms the system from "unformable" to "formable".
[0076] Meanwhile, the coefficient of linear expansion in Example 1 (13.6 × 10⁻⁶) -6 / K) is not superior to Comparative Example 2 (13.2 × 10 -6 / K); however, after three reflow soldering cycles at 260℃, the center distance offset of the guide pin holes in Example 1 was 0.58μm, far lower than the 1.35μm in Comparative Example 2, representing a reduction of approximately 57%. This indicates that the improvement in hole stability achieved by the present invention is not through reducing the coefficient of linear expansion, but rather stems from the fact that the infusible organic microspheres maintain a rigid particle morphology at a reflow temperature of 260℃ (its Tg=345℃, approximately 85℃ higher than the reflow temperature), forming a thermally stable rigid framework together with the spherical inorganic microspheres, thus constraining the thermal deformation of the matrix during the reflow process.
[0077] 4.2 The necessity of infusible organic microspheres Comparative Example 3 used fusible polyetherimide microspheres with a glass transition temperature of 217°C instead of the crosslinked polyimide microspheres of the present invention. Although it had the lowest melt viscosity (470 Pa·s) and good formability, under reflow soldering conditions at 260°C, the organic microspheres softened or even melted far above their glass transition temperature, losing their particle morphology and skeletal support capabilities. This resulted in a pore displacement of up to 2.35 μm after reflow, the worst among all samples, and the largest displacement increment after thermal aging (0.62 μm). This comparative example demonstrates that not all organic microspheres can achieve the effects of the present invention; they must have a glass transition temperature of not less than 300°C and must not have a melting endothermic peak, i.e., they must maintain "non-fusibility".
[0078] It should be noted that the lower melt viscosity of Comparative Example 3 compared to Example 1 does not necessarily mean superior processing fluidity. Since the glass transition temperature of the polyetherimide microspheres is only 217°C, they are already in a molten state under viscosity testing conditions at 340°C and no longer exist as rigid solid particles. Therefore, in Comparative Example 3, only spherical silica actually serves as the rigid filler, and its effective solid volume fraction is lower than that of Example 1. Simultaneously, the molten polyetherimide is dispersed in the system in a liquid phase, and its deformation under shear can also reduce the apparent viscosity. Consequently, Comparative Example 3 loses the support of the rigid particle skeleton under reflow soldering conditions at 260°C, resulting in the most severe pore displacement.
[0079] 4.3 The necessity of particle size window for organic microspheres The organic microspheres of Comparative Example 4 have a D50 of 0.08 μm (1.0 times that of the fine peak D50, below the lower limit of 1.5 times). Due to their small particle size, they agglomerate on their own and cannot serve as a dispersion medium or enter the target layer between the medium and coarse peaks. As shown in Table 2, the tap density of the pre-packed aggregate (1.66 g / cm³) is only 0.6% higher than that of the spherical inorganic microspheres alone (1.65 g / cm³), which does not reach the 1.05 times required by this invention, and the packing density is not substantially improved. The melt viscosity rises to 700 Pa·s and short shots occur, with a pore position shift of 1.28 μm.
[0080] The organic microspheres of Comparative Example 5 have a D50 of 0.96 μm (0.8 times the D50 of the mid-peak, higher than the upper limit of 0.5 times). Due to their excessively large particle size, they cannot enter the gaps formed by the accumulation of mid-peak and coarse-peak particles, and can only exist as additional coarse particles. As shown in Table 2, the tap density of its pre-stacking aggregate (1.67 g / cm³) is only 1.2% higher than that of the spherical inorganic microspheres alone (1.65 g / cm³), and also does not reach 1.05 times. Since the organic microspheres can only be sparsely distributed in the matrix, with too large a distance between them, they cannot form a dense rigid skeleton together with the spherical inorganic microspheres. Therefore, although the melt viscosity is reduced to 490 Pa·s, the pore displacement is still 1.15 μm, which is significantly worse than the 0.58 μm of Example 1.
[0081] Comparative Examples 4 and 5 define the range of D50 values for the organic microspheres of the present invention from the lower and upper limits, respectively, proving that "D50 is 0.15 to 0.5 times that of the mid-peak and 1.5 to 8 times that of the fine-peak" is not a conventional choice, but a necessary condition for achieving pre-packaging densification and skeleton continuity.
[0082] 4.4 The Necessity of Tri-peak Gradation and Two-Stage Process Comparative Example 6 uses single-peak spherical silica (D50=9μm), which lacks the interstitial filling of fine and medium peaks, resulting in a significant decrease in packing density, a melt viscosity as high as 760Pa·s, and the occurrence of short shots. The coefficient of linear expansion and the pore position offset are also among the worst levels, proving that the three-peak gradation is the basis for achieving high filling and low viscosity.
[0083] Comparative Example 8 omitted the S1 low-temperature pre-stacking section, and all components were melt-blended at 310°C in a single process. Due to the lack of a solid-state pre-stacking process, the infusible organic microspheres could not function as a dispersion medium, and the agglomeration of nano-peaks was not effectively eliminated. Its melt viscosity (595 Pa·s) was higher than that of Example 1 (558 Pa·s), and its pore position shift (0.98 μm) was also significantly worse than that of Example 1 (0.58 μm), proving that the S1 low-temperature pre-stacking section is necessary to achieve the dense packing and pore position stability of the present invention.
[0084] 4.5 The necessity of asymmetric interfaces (organic microspheres without surface treatment) Example 5 only treated spherical inorganic microspheres with silane. The resulting composite material had a pore displacement of 0.50 μm and a flexural strength of 172 MPa, which were the best values among all samples. This shows that silane treatment on the inorganic side helps to improve interfacial bonding and mechanical properties.
[0085] Comparative Example 7, based on Example 5, further applied phenyltrimethoxysilane to the infusible organic microspheres to create a coupling agent layer on their surface. The results showed that the melt viscosity increased from 558 Pa·s in Example 1 to 590 Pa·s. More importantly, the pore displacement after reflux worsened from 0.58 μm in Example 1 to 1.05 μm, a degradation of approximately 81%, approaching the levels of Comparative Example 1 (pure inorganic system, 1.62 μm) and Comparative Example 8 (one-step method, 0.98 μm).
[0086] The inventors believe the reason is that the physical interface between the infusible organic microspheres and the polyphenylene sulfide matrix has a certain interfacial slip capability. During the thermal cycling process of reflow at 260°C, thermal stress can be relaxed through limited interfacial slip, avoiding stress concentration and accumulation at the interface, thereby inhibiting the cumulative drift of pore sites. Once a coupling agent or compatibilizer is applied to this interface, the interface is anchored and loses its slip capability, thermal stress cannot be relaxed, and instead, pore site displacement is significantly worsened. This phenomenon is contrary to the conventional teaching in the art that "fillers should all be coupled to improve interfacial bonding," and constitutes the basis for the asymmetric interface design of this invention.
[0087] Therefore, in this invention, the silane coupling agent layer is only disposed on the surface of the spherical inorganic microspheres, while the surface of the infusible organic microspheres does not contain the coupling agent layer or compatibilizer, and it maintains a physical contact interface with the polyphenylene sulfide matrix.
[0088] 4.6 Advantages of Resveratrol-Based Bio-based Epoxy Resin Microspheres in Resveratrol's Resistance to Thermo-oxidative Aging As shown in Table 3, Example 4 uses resveratrol-based bio-based epoxy resin microspheres, and its conventional rigidity and dimensional stability indicators are basically equivalent to those of Example 1, which uses cross-linked polyimide microspheres. Both meet the requirement that the pore position offset is no more than 1.0 μm. However, Example 4 shows a much better effect than Example 1 in terms of resistance to thermo-oxidative aging.
[0089] As shown in Table 4, the oxidation induction period of Example 4 reached 42 min, which is 2.3 times that of Example 1 and 3.5 times that of Comparative Example 1, a pure inorganic system. Its melt viscosity change rate after being kept at 340℃ for 30 min was only +7%, while that of Example 1 was +22% and that of Comparative Example 1 was +28%. After long-term heat aging at 175℃ for 1000 h, the flexural strength retention rate of Example 4 was 93%, which is significantly higher than that of Example 1 (78%) and Comparative Example 1 (68%). Correspondingly, the pore displacement increment after heat aging at 150℃ for 1000 h was only 0.06 μm, which is lower than that of Example 1 (0.12 μm).
[0090] The aforementioned effects stem from the polyphenolic structure in the resveratrol molecular skeleton: resveratrol is 3,5,4'-trihydroxystilbene, and the bio-based epoxy resin prepared from it retains phenolic hydroxyl groups capable of capturing free radicals after cross-linking and curing (the phenolic hydroxyl content of the variety used in Example 4 was 0.82 mmol / g). Polyphenylene sulfide undergoes thermo-oxidative degradation and oxidative cross-linking during melt processing at 290~340℃ and long-term high-temperature use, manifested as melt viscosity drift, discoloration, and mechanical degradation after long-term aging; the phenolic hydroxyl groups retained in the microspheres can capture free radicals generated during this process, interrupt the chain oxidation reaction, and thus inhibit the aforementioned degradation.
[0091] Comparative Example 9 replaced the resveratrol-based epoxy resin microspheres in Example 4 with an equal mass of cross-linked bisphenol A type epoxy resin microspheres (phenolic hydroxyl content only 0.03 mmol / g, glass transition temperature 300℃, D50 0.35μm, also infusible microspheres). The results showed that the oxidation induction period of Comparative Example 9 decreased to 20 min, the viscosity change rate at 340℃×30 min increased to +20%, and the strength retention rate at 175℃×1000 h decreased to 79%, which was essentially equivalent to Example 1 (cross-linked polyimide system), but significantly inferior to Example 4. This indicates that the thermo-oxidative aging resistance observed in this invention does not originate from the organic microspheres or epoxy resin microspheres themselves, but specifically from the phenolic hydroxyl groups retained in the resveratrol polyphenol structure.
[0092] Therefore, in this invention, when cross-linked resveratrol-based bio-based epoxy resin microspheres are used as infusible organic microspheres, in addition to achieving the aforementioned low coefficient of linear expansion and 260°C reflow soldering hole stability, the processing thermal stability and long-term resistance to thermo-oxidative aging of the composite material can also be significantly improved, constituting a preferred technical solution that combines dimensional stability and durability.
[0093] V. Conclusion As shown in Tables 1 to 4 and the above analysis, this invention, through a specific combination of "trimodal spherical inorganic microspheres + infusible organic microspheres," combined with a two-stage preparation process of "low-temperature pre-stacking—high-temperature infiltration" and an asymmetric interface design, maintains the melt viscosity at 340℃ and 900s. - ¹While achieving a precision-formable window with a pressure not exceeding 600 Pa·s, the center distance offset of the guide pin hole after reflow soldering at 260℃ is controlled within 0.50~0.85μm, which is significantly better than that of the pure inorganic system (1.35~1.95μm) and the fusible organic microsphere system (2.35μm), thus achieving a balance between low linear expansion coefficient, high hole stability and good forming fluidity.
[0094] The above embodiments are merely illustrative of the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to the preferred embodiments above, those skilled in the art should understand that modifications or equivalent substitutions to the technical solutions of the present invention should not depart from the spirit and scope of the present invention. Those skilled in the art can also make other changes within the spirit of the present invention and use them in the design of the present invention, as long as they do not deviate from the technical effects of the present invention. These changes made according to the spirit of the present invention should all be included within the scope of protection claimed by the present invention.
Claims
1. A modified polyphenylene sulfide composite material, characterized in that, Including polyphenylene sulfide, spherical inorganic microspheres and infusible organic microspheres; Based on 100 parts by weight of polyphenylene sulfide, the spherical inorganic microspheres are 280-450 parts, and the infusible organic microspheres are 2-40 parts; The spherical inorganic microspheres have three particle size peaks: fine peak, medium peak, and coarse peak, with D50 values of 60–100 nm, 0.5–2.5 μm, and 5–15 μm for the fine, medium, and coarse peaks, respectively. The glass transition temperature of the infusible organic microspheres is not lower than 300°C, and the D50 of the infusible organic microspheres is 0.15 to 0.5 times that of the middle peak and 1.5 to 8 times that of the fine peak.
2. The modified polyphenylene sulfide composite material according to claim 1, characterized in that, The infusible organic microspheres are at least one of cross-linked polyimide or its copolymer microspheres, bio-based epoxy resin microspheres, and polysulfonated aromatic amide.
3. The modified polyphenylene sulfide composite material according to claim 2, characterized in that, The infusible organic microspheres are cross-linked polyimide microspheres, with a sphericity ≥0.85 and a particle size distribution span (D90). D10 / D50 ≤ 1.5; the gel content of the cross-linked polyimide microspheres is ≥ 85%.
4. The modified polyphenylene sulfide composite material according to claim 2, characterized in that, The infusible organic microspheres are cross-linked resveratrol-based bio-based epoxy resins, and the phenolic hydroxyl content of the bio-based epoxy resins is not less than 0.5 mmol / g.
5. The modified polyphenylene sulfide composite material according to claim 1, characterized in that, The spherical inorganic microspheres are selected from one or more of alumina, silicon oxide, and magnesium aluminate, and the sphericity of the spherical inorganic microspheres is ≥0.90, and the sphericity of the coarse peaks is ≥0.
93.
6. The modified polyphenylene sulfide composite material according to claim 5, characterized in that, The surface of the spherical inorganic microspheres has a silane coupling agent layer, and the amount of silane coupling agent in the silane coupling agent layer is 0.5 to 12 parts per 100 parts by weight of polyphenylene sulfide.
7. The modified polyphenylene sulfide composite material according to claim 1, characterized in that, The fine peaks, medium peaks, and coarse peaks account for 5%–15%, 20%–35%, and 50%–70% of the total volume of the spherical inorganic microspheres, respectively; the sum of the volume fractions of the fine peaks, medium peaks, and coarse peaks is 100%.
8. The modified polyphenylene sulfide composite material according to claim 7, characterized in that, The ratio of the D50 of the medium peak to the D50 of the coarse peak is 1:2 to 1:30, and the ratio of the D50 of the fine peak to the D50 of the medium peak is 1:5 to 1:
50.
9. A method for preparing the modified polyphenylene sulfide composite material according to any one of claims 1 to 8, characterized in that, This includes a low-temperature pre-stacking section and a high-temperature impregnation section performed sequentially: S1. Spherical inorganic microspheres and infusible organic microspheres are mixed in a twin-screw extruder at 120~200℃, 50~200r / min and residence time of 60~300s to obtain a pre-packed particle aggregate. The tap density of the pre-packed particle aggregate is not less than 1.05 times the tap density of the spherical inorganic microspheres alone. S2. Polyphenylene sulfide is added and melted through the main feed port of the twin-screw extruder. The pre-stacked particle aggregate is added to the molten polyphenylene sulfide through a side feed port located after the melting section. The mixture is blended at 290–340°C, with a screw speed of 200–600 r / min, a residence time of 30–180 s, and a melt average shear rate of 500–5000 s. - ¹, when the vacuum degree ≤ Exhaust gas at 0.06 MPa and extrude pellets.
10. The method according to claim 9, characterized in that, It also includes S3: after drying the pellets obtained by pelletizing at 120-140℃ for ≥4h, they are injection molded, and then annealed at 190-215℃ for 30-180min with a cooling rate of 10-40℃ / h.
Citation Information
Patent Citations
MT ferrule and its preparation method and application
CN114350151B
Ferrule for optical connector, mold for ferrule, method of manufacturing ferrule for optical connector, and method of testing ferrule for optical connector
EP1031859A1
Optical ferrule
US6347890B2